Diseño y construcción de un Kiosko electrónico prototipado para la impresión automática de certificados académicos para los estudiantes del Área de la Energía, las Industrias y los Recursos Naturales no Renovables. - Jadán Patiño, Alexandra Esperanza, Mayra Vanessa Loja Sandoya (2016)
This thesis deals with the theme : "Design and Construction of an Electronic Kiosk Prototyping for Automatic Printing Certificates for Students Academic Area Energy Industries and Non- Renewable Natural Resources", whose main objective is to create a tool information that will improve services broadcast transcripts capable of meeting the requirements of students AEIRNNR . For the design of the tool were performed: diagram use cases, class diagrams and sequence diagrams with the help of Enterprise Architect, a platform for modeling software to analyze, design and document applications, and offering a detailed way to generate the physical data model. As NetBeans 6.5 programming environment which supports the surprising and prototype javascript library jQuery with which developed the solution plus some snippets of php and latex is used also allows the use of pattern MVC (Model-View -Driver) needed for web design. The implementation of the Jquery library containing common functionalities of DOM, events, effects and AJAX is a fundamental tool in building application allowing you to create effects and custom animations. With all these tools is able to build the application and its operation has been duly confirmed by the users of the Universidad Nacional de Loja.